2022
DOI: 10.1101/2022.11.09.514848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event-Related Desynchronization induced by Tactile Imagery: an EEG Study

Abstract: It is well known that both the movement of the hand itself and the mental representation of it lead to event-related desynchronization (ERD) of EEG recorded over the corresponding motor areas of the cerebral cortex. Similarly, in somatosensory cortical areas, ERD occurs upon tactile stimulation of the hand, but whether this effect is caused by mental representation of sensations from tactile stimulation remains poorly understood. In the present study, the effects on the EEG of imaginary vibrotactile sensations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 75 publications
(87 reference statements)
3
11
0
Order By: Relevance
“…In this study, we complemented the previous findings, where changes in EEG rhythms were found during TI (12,16,17), with the demonstration that TI effects on the TMS-evoked responses in the forearm and hand muscles were different from those of kMI and TS.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In this study, we complemented the previous findings, where changes in EEG rhythms were found during TI (12,16,17), with the demonstration that TI effects on the TMS-evoked responses in the forearm and hand muscles were different from those of kMI and TS.…”
Section: Discussionsupporting
confidence: 78%
“…During the TI task, participants were asked to mentally reproduce the sensations experienced during the vibrotactile stimulation (12,17). Before the TI trials, participants were also acquainted with the tactile sensations produced by stimulation with a brush of the proximal parts of index, middle, ring and little fingers and distal part of the palm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that somatosensory stimuli, which differs in its pattern or type, induces other patterns of cortical activity [63], [64], [65], [66]. In addition, imagery and execution of somatosensory stimulation can facilitate cortical excitability [67], [68]. In this study, our results for HC II also indicated that the EEG activities (deactivation) at somatosensory area (CPz) appeared strong not only in poor performers, but also good performers.…”
Section: Novel Hybrid-approach To Enhance Bci Performance In Bci-inef...supporting
confidence: 69%